Manajemen Kurikulum Merdeka pada Madrasah Inklusi - Murodah, Nelli; Riska Mutiara, Mela (Al-Riwayah : Jurnal Kependidikan, 2024)
This research is a qualitative study which aims to analyze the planning, organization, implementation and evaluation model of the independent curriculum at inclusive madrasas at MI Walisongo Kranji 01 Kedungwuni. Data was collected through interviews, observation and documentation. Meanwhile, data analysis uses the interactive analysis model proposed by Miles and Hubermen. The results show that: 1) Curriculum planning includes discussions between the madrasa head and the madrasa coordinator. This discussion is carried out before a meeting is held with the teacher to discuss activity plans in the learning process using the applied curriculum, 2) Organizing the curriculum includes choosing the right homeroom teacher in the new school year, then designing the lessons that will be delivered, 3) Implementing the curriculum in the form of appropriate learning carried out by the teacher, and this is the responsibility of the class teacher and subject teacher. As for children with special needs, there is an Individual Learning Program (PPI) that has been scheduled, and 4) In curriculum evaluation there are three stages of assessment or assessment which include, diagnostic assessment, formative assessment, and summative assessment. However, in summative assessments related to report card grades, there are differences for students with special needs and normal students. The difference lies in the type of questions given. For normal students, the types of questions include multiple choice, essay and description. Meanwhile, for students with special needs, the types of questions include multiple choice, draw the line, and true-false questions.